1973
DOI: 10.1113/jphysiol.1973.sp010223
|View full text |Cite
|
Sign up to set email alerts
|

Possible screening of surface charges on crayfish axons by polyvalent metal ions

Abstract: SUMMARY1. The effect of different polyvalent metal ions in the external solution upon the threshold membrane potential for spike initiation in crayfish axons has been studied by means of intracellular micro-electrodes. The metal ions tested included six divalent cations (Ca2+, Mg2+, Sr2+, Ba2+, Co2+, and Ni2+) and three trivalent cations (La +, Y3+ and Eu3+).2. Identical extracellular concentrations of different cations with the same valence had essentially the same effect on threshold membrane potential. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The threshold of the action potential was shifted to less negative values. This finding agrees with the results on crayfish axon given by D'Arrigo (1973).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…The threshold of the action potential was shifted to less negative values. This finding agrees with the results on crayfish axon given by D'Arrigo (1973).…”
supporting
confidence: 94%
“…The trivalent rare earth alkaline cation lanthanum has been shown to affect ion permeabilities in nerve and the activation of contraction in skeletal muscle in a similar way as calcium (Takata et al, 1966;Blaustein & Goldman, 1968;D'Arrigo, 1973;Hartz & Ulbricht, 1973;Andersson & Edman, 1974b;D6rrscheidt-Kiifer & Ltittgau, 1974;Vogel, 1974). These authors reported a shift in sodium and potassium permeability curves to less negative potentials in a variety of nerve preparations at relatively low [La3+l o (<1 raM), and an eventual block of action potential conductance after longer application or at concentrations of ca.…”
Section: Discussionmentioning
confidence: 92%
“…The explanation for this effect may be that Ba, having nearly the same crystal or singly hydrated radius as K, may plug K § channels in the membrane (Mullins, 1961;Werman & Grundfest, 1961;Sperelakis & Lehmkuhl, 1966;Krnjevic, Pumain & Renaud, 1971). The effect of Ba on some axons appears to be very similar to that of Ca (Narahashi, 1966;Blaustein & Goldman, 1968;D'Arrigo, 1973). Fatt and Ginsborg (1958), Hagiwara and Naka (1964), and Hagiwara, Fukuda and Eaton (1974) regard Ba as an efficient carrier of the inward current through the Ca channel in crustacean muscle fibers.…”
mentioning
confidence: 77%
“…5b We started on the basis of the hypothesis that surface potential affects the conductance of the outer border sodium channel (Grinstein et al, 1978;Goudeau et al, 1979). If such a negative surface potential (Naharashi, 1966;Ito, Kuriyama & Tashiro, 1970;D'Arrigo, 1973) is reduced by La 3+ on the outer side of the membrane, this leads to an increase in the intramembrane inward electrical field. In view of the above evidence of the voltage dependency of the apical border sodium conductance (with an increased conductance when the cell hyperpolarizes) such a La 3 +-induced rise in the electrical field could produce the observed sodium conductance increase.…”
Section: Effects Of La 3+mentioning
confidence: 99%